Adaptive Cooperative Attitude Control of Satellite Formation System via Fractional-Order PID - Kui, Qixin; Li, Xiaolei; Ju, Yinhao; Wu, Ruihang; Liu, Jiawei (Journal of physics. Conference series, 2025)
This paper presents a novel robust attitude cooperation scheme that integrates an adaptive cooperative strategy with fractional-order PID for satellite formation systems subject to external disturbances. Firstly, the theoretical foundations for the attitude dynamics model of the considered satellites are derived. Secondly, to achieve attitude cooperation, a cross-coupled attitude cooperative error is designed, where adaptive weighting dynamically regulates cooperative performance among multiple satellites. Thirdly, a fractional-order PID controller is developed based on the adaptive cooperation strategy, which significantly reduces system chattering and improves the attitude cooperation between satellites while ensuring fast attitude convergence. Finally, numerical simulations validate the effectiveness of the presented controllers under disturbance scenarios.